Dysregulation of VEGF-dependent angiogenesis in cavernous lung tuberculosis. Issue 3 (September 2019) - Golubinskaya, E.P.; Filonenko, T.G.; Kramar, T.V.; Yermola, Yu.A.; Kubyshkin, A.V.; Gerashenko, A.V.; Kalfa, M.A.; Shramko, Iu.I.
Abstract: Introduction: Tuberculosis (TB) remains one of the most dangerous infections with the high mortality in the whole world. The leading problems in the modern course of TB are both long-term therapy and appearance of multiplying and wide resistant forms, as well as the rise of comorbid pathology (e.g. AIDS-associated TB). Nonefficient antibiotic therapy forces the search of alternative ways of treatment. Prospective among existent ones is "target therapy" aimed on key links in a host organism. The aim of our study was to determine the morphofunctional characteristics of VEGF-A dependent angiogenesis in patients with fibrous-cavernous pulmonary tuberculosis, depending on the activity of dischargein order to justify the use of angiogenesis blockers. Methods: Material for research were the fragments of the cavities' wall and pericavernous lung tissue of deceased or operated patients about fibro-cavernous tuberculosis with active bacillation (n = 89) and with clinical abacillation (n = 74). To assess the activity of VEGF-A-dependent angiogenesis, we used an immunohistochemical study with markers CD68, VEGF-A, CD34 and CollagenIV, followed by determination of the vascular perfusion index. Results: Hyperactivation of VEGF-A dependent angiogenesis in the foci of specific inflammation leads to the dysregulation of the formation in functionally complete vessels and the creation of the most comfortable conditions for the persistence of M. tuberculosis in the form of sufficient aeration in the area of specific granulations, while reducing the vascular permeability of the fibrous layer vessels, providing inefficient recruitment of cells of the immune system and targeted delivery of drugs. In the pericavernous zone and intact pulmonary tissue, hyperexpression of VEGF-A leads to aggravation of local pulmonary hypertension, increase of tissue hypoxia, fibrous remodeling of the aero-hematic barrier and the formation of the alveolar-capillary block, which is a morphofunctional indicator of respiratory failure. Conclusions: Taking into account the absolute prevalence of proangiogenic factors in FCT in all patients, the use of targeted therapy aimed at VEGF-A blockade is pathogenetically justified.